Membrane lipid profile monitored by mass spectrometry detected differences between fresh and vitrified in vitro-produced bovine embryos - Leão, Beatriz Caetano da Silva [UNESP]; Rocha-Frigoni, Nathalia Alves de Souza [UNESP]; Cabral, Elaine Cristina; Franco, Marcos Fernando; Ferreira, Christina Ramires; Eberlin, Marcos Nogueira; Filgueiras, Paulo Roberto; Mingoti, Gisele Zoccal [UNESP] (Cambridge University Press, 2015)
This study aimed to evaluate the impact of vitrification on membrane lipid profile obtained by mass spectrometry (MS) of in vitro-produced bovine embryos. Matrix-assisted laser desorption ionization-mass spectrometry (MALDI-MS) has been used to obtain individual embryo membrane lipid profiles. Due to conditions of analysis, mainly membrane lipids, most favorably phosphatidylcholines (PCs) and sphingomyelins (SMs) have been detected. The following ions described by their mass-to-charge ratio (m/z) and respective attribution presented increased relative abundance (1.2-20×) in the vitrified group: 703.5 [SM (16:0) + H]+; 722.5 [PC (40:3) + Na]+; 758.5 [PC (34:2) + H]+; 762.5 [PC (34:0) + H]+; 790.5 [PC (36:0) + H]+ and 810.5 [PC (38:4) + H]+ and/or [PC (36:1) + Na]+. The ion with a m/z 744.5 [PCp (34:1) and/or PCe (34:2)] was 3.4-fold more abundant in the fresh group. Interestingly, ions with m/z 722.5 or 744.5 indicate the presence of lipid species, which are more resistant to enzymatic degradation as they contain fatty acyl residues linked through ether type bonds (alkyl ether or plasmalogens, indicated by the lowercase 'e' and 'p', respectively) to the glycerol structure. The results indicate that cryopreservation impacts the membrane lipid profile, and that these alterations can be properly monitored by MALDI-MS. Membrane lipids can therefore be evaluated by MALDI-MS to monitor the effect of cryopreservation on membrane lipids, and to investigate changes in lipid profile that may reflect the metabolic response to the cryopreservation stress or changes in the environmental conditions.
Keywords: Bovine embryo; In vitro production; Lipid profile; Mass spectrometry; Vitrification